Characteristics and determinants of population acceptance of COVID-19 digital contact tracing: a systematic review - Pegollo, Leonardo; Maggioni, Elena; Gaeta, Maddalena; Odone, Anna (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: As recently outlined in the WHO-ECDC Indicator framework (1) to evaluate the public health effectiveness of digital proximity tracing solutions, one of the main barriers to digital contact tracing (DCT) is population acceptance, which, in turns, is influenced by digital literacy, attitudes and practice. DCT came to public prominence during the COVID-19 pandemic but evidence on its population acceptance have not been comprehensively analyzed. Methods: We carried out a systematic review (PROSPERO: CRD42021253668) following the PRISMA guidelines to collect, systematize and critically appraise the available evidence on population DCT acceptance. Original studies reporting on different measures of population DCT acceptance were included. Conclusions: The systematic review was based on 41 articles meeting our a priori defined inclusion criteria, comprising aa total of 186144 surveyed subjects, 50000 tweets, 5025 Reddit posts and 714 written comments. Data extraction and synthesis required a qualitative outcome grouping, performed ex-post, in 14 different benchmarks components. They constitute a narrative analysis of actionable points for public health policy. Population acceptance is a key component of DCT effective adoption and infection control during infectious diseases outbreaks. Assessing DCT acceptance’s determinants in different settings, populations an cultural contexts it is of fundamental importance to inform the planning, implementation and monitoring of public health interventions. The results of our in-depth qualitative and quantitative analysis will provide context for prospective improvements and actionable items and should guide future research aimed at exploring how digitalization can serve people-centred care.